EXPLORATION OF ETHNOMATHEMATICS RULES ON TRADITIONAL FOOD KEI PEOPLE SOUTHEAST MOLUCAS - Helen Johana Dumatubun (Sean Institute, 2022)
This research aims to explore ethnomathematics rules in the traditional food of the Kei people of Southeast Molucas, so that it can be used as a source of school mathematics learning to overcome the difficulties faced by students in understanding mathematical concepts. The type of research used is qualitative descriptive research. The results showed that in the traditional food of the Kei community in Southeast Molucas contains ethnomathematics rules, namely the concept of fractions, addition and reduction of fractions, parallelogram, beams, tubes, cones, beheaded cones and the volume of rotary object.